2020
DOI: 10.3892/ijo.2020.5153
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between YAP and TGFβ regulates SERPINE1 expression in mesenchymal lung cancer cells

Abstract: Serpin family E member 1 (SERPINE1), a serine proteinase inhibitor, serves as an important regulator of extracellular matrix remodeling. Emerging evidence suggests that SERPINE1 has diverse roles in cancer and is associated with poor prognosis. However, the mechanism via which SERPINE1 is induced in cancer has not been fully determined. In order to examine the molecular mechanism of SERPINE1 expression, the present study took advantage of the isogenic pair of lung cancer cells with epithelial or mesenchymal fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…In vitro modeling confirmed that TAZ is necessary for TGF-β1-mediated fibrogenesis and vector-driven TAZ synthesis mimics aspects of the TGF-β1-induced phenotype including G 2 /M arrest and acquisition of a profibrotic program [ 27 ]. TAZ is required for maximal TGF-β1-mediated expression of the SMAD target gene encoding plasminogen activator inhibitor-1 (PAI-1), a potent profibrotic clade E member of the serine protease inhibitor family (SERPINE1) [ 27 , 28 , 29 , 30 ], and a similar involvement of YAP in TGF-β1-induced PAI-1 expression is evident in lung tumor cells [ 31 ]. KEGG analysis confirmed, moreover, that convergence of the TGF-β and Hippo signaling pathways regulates transcription of the fibrosis-inducing connective tissue growth factor (CTGF; CCN2) and SERPINE1 genes [ 32 ] ( Figure 1 ).…”
Section: Cancer-associated Fibroblasts: Biology Of the Fibrotic Tumor...mentioning
confidence: 99%
“…In vitro modeling confirmed that TAZ is necessary for TGF-β1-mediated fibrogenesis and vector-driven TAZ synthesis mimics aspects of the TGF-β1-induced phenotype including G 2 /M arrest and acquisition of a profibrotic program [ 27 ]. TAZ is required for maximal TGF-β1-mediated expression of the SMAD target gene encoding plasminogen activator inhibitor-1 (PAI-1), a potent profibrotic clade E member of the serine protease inhibitor family (SERPINE1) [ 27 , 28 , 29 , 30 ], and a similar involvement of YAP in TGF-β1-induced PAI-1 expression is evident in lung tumor cells [ 31 ]. KEGG analysis confirmed, moreover, that convergence of the TGF-β and Hippo signaling pathways regulates transcription of the fibrosis-inducing connective tissue growth factor (CTGF; CCN2) and SERPINE1 genes [ 32 ] ( Figure 1 ).…”
Section: Cancer-associated Fibroblasts: Biology Of the Fibrotic Tumor...mentioning
confidence: 99%
“…Exposure of HK2 cells to hypoxic stress similarly promotes G 2 /M stalling and PAI-1 induction while TAZ overexpression leads to the accumulation of HK-2 cells in G 2 /M phase. TAZ is, in fact, required for maximal TGF-β1-mediated PAI-1 synthesis in proximal tubular cells (Liu et al, 2015;Samarakoon et al, 2015;Anorga et al, 2018;Bessho et al, 2019) and a similar involvement of YAP in TGF-β1induced PAI-1 expression is evident in lung tumor cells (Kong et al, 2021). KEGG analysis confirmed that convergence of the TGF-β and Hippo signaling pathways regulates transcription of the profibrotic CCN2 and SERPINE1 genes (Figure 7).…”
Section: Injury-associated Acquisition Of a Senescence-like Phenotypementioning
confidence: 68%
“…Importantly, we determined that ten of the 41 genes were downregulated following AHR inhibition in GBMO-30 and significantly associated with survival supporting a role of inactivation of AHR on potential genes that drive mortality in GBM. These include PLP2 , a gene involved in autophagy and ER stress in GBM 32 ; SGMS2, which is associated with aggressive breast cancer 33 ; MT1H, which is a tumor suppressor in liver cancer 34 ; and SERPINE1 , which is associated with several cancers 35 ( Fig. 7b- e ).…”
Section: Resultsmentioning
confidence: 99%